The effect of workload on burnout syndrome among nurses - Mitha Rahmilah; Meliana Handayani; Wa Ode Maghfira Nurul Insani (JOURNAL OF Mental Health Concerns, 2026)
Background: Burnout syndrome is a condition of physical, emotional, and mental exhaustion caused by prolonged work stress, which is commonly experienced by nurses. High demands in health service delivery place nurses at risk of burnout, especially when accompanied by heavy workloads. Purpose: To determine the effect of workload on burnout syndrome among nurses. Method: A quantitative design with a cross‑sectional approach was used. The study population consisted of 234 nurses, with a sample of 146 respondents selected using simple random sampling. Data were collected using the Maslach Burnout Inventory–Human Services Survey (MBI‑HSS) to measure burnout syndrome and the NASA‑TLX to assess workload. Data analysis was conducted using Pearson Chi‑Square test. Results: The results showed that the majority of respondents had a high workload (100 respondents, 68.5%) and the majority experienced burnout syndrome in the moderate category (94 respondents, 64.4%). The statistical test yielded a p‑value of 0.943 (p > 0.05), indicating no significant relationship between workload and burnout syndrome among nurses. Conclusion: Burnout syndrome among nurses is not influenced solely by workload, but also by other factors such as social support, work environment, motivation, and individual capacity in managing work stress. Keywords: Burnout Syndrome; Health; Hospital; Nurses; Workload.